BIMBINGAN GURU MADRASAH DALAM MENINGKATKAN KECERDASAN SPIRITUAL PELAJAR MELALUI PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH SWASTA AMALIYAH TANJUNG TIGA - M. Baihaqi (PUBLICA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This devotional article describes the guidance of madrasa teachers in improving the spiritual intelligence of students through Islamic religious education at the Amaliyah Tanjung Tiga Private Madrasah Aliyah. The purpose of this service is to educate and inform readers that spiritual intelligence can be obtained if students are educated at madrasa educational institutions. The dedication method is the field method (qualitative), namely the author is in direct contact with students. The approach used is an anthropological and sociological approach. Data collection techniques are through observation and unstructured interviews with informants who are considered to have competence, after which the data is obtained and then the data is analyzed scientifically. The location of the community service activities is in the Tanjung Tiga Amaliyah Private Madrasah Aliyah. The results of the community service activities show that: First, students are educated with the knowledge of faith and muamalah, second, Making norms or rules based on the rules of Islamic law in the madrasah environment so that students become educated, Third, developing spiritual intelligence through religious education subjects Islam on students is carried out using the teacher's approach as an example to students.